America's bitter pill : money, politics, backroom deals, and the fight to fix our broken healthcare system - Brill, Steven, frey50 (New York Random House, 2015)
"America's Bitter Pill is Steven Brill's much-anticipated, sweeping narrative of how the Affordable Care Act, or Obamacare, was written, how it is being implemented, and, most important, how it is changing--and failing to change--the rampant abuses in the healthcare industry. Brill probed the depths of our nation's healthcare crisis in his trailblazing Time magazine Special Report, which won the 2014 National Magazine Award for Public Interest. Now he broadens his lens and delves deeper, pulling no punches and taking no prisoners,"--Amazon.com
Looking up from the gurney -- Center stage -- Max, Barack, Hillary, Billy, and the gathering consensus -- "This is what I thought the Senate would be like" -- A new president commits, and his camp divides -- Every lobbyist's favorite date -- Punting to Capitol Hill -- Deal time -- Behind closed doors : White House turf wars, industry deals, and Senate wrangling -- The Tea Party summer, "I'm feeling lucky," and "You lie" -- Snow jobs, poison pills, and Botox -- New trouble, then Mount Everest -- In Washington "everything is slipping," but not in Kentucky -- An Office becomes a Center-and it matters -- Meantime, outside the beltway... -- Waiting for Obamacare -- A guy in jeans, red lights, and a "train wreck" -- Two months to go -- Thirty days to go -- The crash -- Meltdown in D.C., dancing on eight toes in Kentucky, and frustration in Ohio -- The rescue -- The finish line -- Stuck in the jalopy.
Keywords: United States; Medical care. -- Affordable Care Act -- Obamacare; Medical policy -- United States; Health care reform -- United States; Health insurance -- Law and legislation -- United States